Uric Acid Has Different Effects on Spontaneous Brain Activities of Males and Females: A Cross-Sectional Resting-State Functional MR Imaging Study - Lin, Li; Zheng, Li Juan; Joseph Schoepf, U.; Varga-Szemes, Akos; Savage, Rock H.; Wang, Yun Fei; Zhang, Han; Zhang, Xin Yuan; Lu, Guang Ming; Zhang, Long Jiang (Frontiers in Neuroscience, 2019)
Objective To explore the relationship among serum uric acid (SUA) levels, human cognition, and spontaneous brain activities by resting-state functional MRI (rs-fMRI). Methods We prospectively recruited 100 subjects (age 58±11 years, 55 females) who underwent fasting blood sampling, cognitive tests and rs-fMRI scans. The subjects were divided into two groups by gender and each gender group was further stratified into three subgroups according to SUA level. The amplitude of low-frequency fluctuation (ALFF) method was applied to assess spontaneous brain activity among groups. Pearson’s correlation analysis was used to investigate the relationships between the mean ALFF values (mALFF) and cognitive tests. Results A total of 97 patients completed the study protocol successfully. Significant differences in age, education level, number connection test (NCT), and word fluency were observed among the three subgroups in males (all P<0.05). Results of group-by-gender interaction were distributed in bilateral pallidum and putamen [voxel P-value <0.001, cluster P-value <0.05, Gaussian random field (GRF)-corrected]. The tendency of SUA effect on mALFF was different in males and females, particularly in corresponding High SUA subgroups (both P<0.001). Among the male subjects, mALFF values of the bilateral pallidum and putamen negatively correlated with attention/executive function. Conclusion Our results suggest that elevated SUA levels have different effects on spontaneous brain activities and cognitive function in males and females. Males with high SUA levels and hyperuricemia are more susceptible to changes in spontaneous brain activities and lower neuropsychological assessment scores, particularly in word fluency tests and number connection test (NCT), compared to females.